2006
DOI: 10.5507/bp.2006.049
|View full text |Cite
|
Sign up to set email alerts
|

Wear Measurement of Retrieved Polyethylene Abg 1 Cups by Universal-Type Measuring Microscope and X-Ray Methods

Abstract: Background:Polyethylene wear is considered a most important part of periprosthetic osteolysis development. Thus, its measurement is central to contemporary orthopaedics.Aims: The aim of this paper was to compare the accuracy of three radiographic techniques for wear measurement. Secondly, the influence of the abduction angle of the cup on measurement accuracy was investigated.Methods: Wear was measured manually in 80 patients by a single observer according to the Livermore, Charnley, and Dorr description. A mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Second, in this study the assessment of wear involved the technique of Dorr and Wan, 38 using twodimensional digital clinical radiographs and templating software. 39 It is true that many studies [54][55][56] have shown the alternative Livermore technique 57 to be more accurate, even though there are studies that support the opposite. 56 We chose to use the Dorr and Wan 38 technique because it is simple to use 55 and we have used it successfully in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, in this study the assessment of wear involved the technique of Dorr and Wan, 38 using twodimensional digital clinical radiographs and templating software. 39 It is true that many studies [54][55][56] have shown the alternative Livermore technique 57 to be more accurate, even though there are studies that support the opposite. 56 We chose to use the Dorr and Wan 38 technique because it is simple to use 55 and we have used it successfully in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…39 It is true that many studies [54][55][56] have shown the alternative Livermore technique 57 to be more accurate, even though there are studies that support the opposite. 56 We chose to use the Dorr and Wan 38 technique because it is simple to use 55 and we have used it successfully in previous studies. 58 Additionally, both the techniques of Livermore and Dorr and Wan were described to measure wear on metal/UHMWPE articulations, and it is easy to modify the Dorr and Wan method for CoC articulations, but not easy to use the Livermore method on radiographs of CoC THRs.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the diameter of the cup and the head are known, it is possible to calculate the linear and volumetric wear using a geometrical "two-sphere model" and a special computational algorithm that also takes into account the original position of the prosthetic head in the cup and the cross-sectional profile of the ABG I cup. The accuracy of the described method was previously assessed in a set of 30 retrieved cups, ranging between 1 and 4 μm and 1-9 mm 3 for linear and volumetric wear, respectively [14]. The reliability of the method has also been previously reported [15].…”
Section: Wear Measurementmentioning
confidence: 99%
“…In our previous studies, we found that a high risk for an increased wear rate was associated with ABG I prosthesis [11]. We also found a significant association between wear rate and severity of osteolysis in ABG I prosthesis, and an unacceptably high rate of aseptic loosening in ABG I cups [12,13].…”
Section: Introductionmentioning
confidence: 67%